2020
DOI: 10.3389/fonc.2020.584974
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bcl-2 Proteins in Acute Myeloid Leukemia

Abstract: B cell lymphoma 2 (BCL-2) family proteins play an important role in intrinsic apoptosis. Overexpression of BCL-2 proteins in acute myeloid leukemia can circumvent resistance to apoptosis and chemotherapy. Considering this effect, the exploration of anti-apoptotic BCL-2 inhibitors is considered to have tremendous potential for the discovery of novel pharmacological modulators in cancer. This review outlines the impact of BCL-2 family proteins on intrinsic apoptosis and the development of acute myeloid leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 118 publications
1
38
0
Order By: Relevance
“…MYC is one of the most prevalent human oncogenes, while HOXA9 is a common driver of leukemia (75,93,94,119). BCL2 is the target of venetoclax, one of the most promising novel therapies for AML (85). Our study clarifies the complex reported interactions between IRF8, HOXA9 and MEF2C/D proteins.…”
Section: Dynamic Behaviors Of Tf and Mediator Punctasupporting
confidence: 57%
See 1 more Smart Citation
“…MYC is one of the most prevalent human oncogenes, while HOXA9 is a common driver of leukemia (75,93,94,119). BCL2 is the target of venetoclax, one of the most promising novel therapies for AML (85). Our study clarifies the complex reported interactions between IRF8, HOXA9 and MEF2C/D proteins.…”
Section: Dynamic Behaviors Of Tf and Mediator Punctasupporting
confidence: 57%
“…We conclude that IRF8 directly activates transcription of MEF2D, while direct targets of MEF2D include key leukemogenic TFs HOXA9 and MYC (Figure 7H). Direct targets of both TFs include other essential genes, including IRF8 regulation of BCL2, an important therapeutic target in AML (85).…”
Section: The Irf8/mef2 Axis Regulates Key Oncogenes In Kmt2ar Amlmentioning
confidence: 99%
“…However, only 20% of the cells were dead after 72 h of treatment, showing a modest efficacy. Multiple studies previously reported cancer cells’ adaptation to therapy and the key role of the anti-apoptotic BCL-2 family proteins in their resistance to cell death ( Reed et al, 1996 ; Mansoori et al, 2017 ; Maji et al, 2018 ; Wei et al, 2020 ). We next sought to study the role of these proteins after trametinib treatment on NALM-6.…”
Section: Resultsmentioning
confidence: 99%
“…It binds and sequesters the pro-apoptotic Bax/Bak proteins and, thus, prevents the release of cytochrome c [98]. Overexpression of the anti-apoptotic factors Mcl-1, Bcl-2 and Bcl-xL in acute myeloid leukaemia [99] and acute lymphocytic leukaemia [100] may be associated dysregulation of apoptosis. The level of the anti-apoptotic protein Mcl-1 was downregulated in a dose-dependent manner after treating MCF-7 cells with compound 10n (0.05, 0.1 and 0.5 μM) for 48 or 72 h. (Figure 10).…”
Section: Effects Of Compound 10n On Tubulin Polymerisation In Mcf-7 Cellsmentioning
confidence: 99%